EDUCATIONAL SUPPORT OF HUMAN EFFICIENCY IN MARKET CONDITIONS - Pobyrchenko, Neonyla A. (Educological discourse, 2014)
This paper describes the pedagogical support disability rights on the basis of market relations. The need for such a support person who is engaged in the labor market due to self-realization activity habitual ways of acting.